Keaneakaragaman Jenis Semut (formicidae) di Kawasan Taman Nasional Gunung Palung Sebagai Sumber Belajar Biologi - Muhammad Reza Sanjaya; Anandita Eka Setiadi; Mahwar Qurbaniah (Jurnal Penelitian Pendidikan IPA, 2024)
Gunung Palung National Park (GPNP) has a diversity of ant, but the information as a source of learning is still lacking. This study aims to determine the diversity of ant species in the TNGP area and its potential as a source of learning. Research using descriptive qualitative method. Sampling used a pitfall trap placed on a line transect that passes through an alluvial soil forest. Collecting data on potential learning resources using the results of a questionnaire. The results showed that there were 90 individuals from 9 ant species specifically Dinomyrmex gigas, Polyrhachis bihamata, Rhytidoponera araneoides, Dolichoderus thoracicus, Axinidris Acholli, Hagensia havilandi, Myrmicaria brunnea, Anonychomyrma myrmex, Notostigma carazzii. The diversity of species of ants has the potential as a source of learning with indicators of clarity of potential (85%), ease of access (58.33%), security (91.66%), time efficiency (75%), cost (91.66%), suitability with learning objectives (100%), clarity of material objectives (100%), and clarity of information disclosed (100%). This research shows that information about ant diversity is very suitable as a source of learning biology, especially in the subjects of biology, biodiversity, and the classification of living things.